Análise da eficácia de treinamento à distância no ambiente corporativo - Fernandes, Marília Carneiro (2016)
This study analyzed the valuation model of knowledge acquired through distance training of a telecommunications company in the city of Uberlandia - MG. For this, the present study aimed to evaluate the gain of knowledge comparing the marks obtained in the pretest and posttest answered by employees during the course and evaluate, through a questionnaire at the end of training in distance education, degree of satisfaction of employees with the new organization design. The first objective was to analyze the company's database with 14.028 participants. As was a large population, this number was divided by the number of courses (14) for a total sample of 1,002 participants. In the evaluation of the questionnaires, which was the second objective of this study, the sample was 343 participants. To evaluate the gain of knowledge comparing the marks obtained in the pre and post-test, he was made a T test notes pre and post-test in the SPSS system. The results showed a gain of knowledge in all courses. In the evaluation of the questionnaires, the results showed that despite being a new methodology, the courses in distance education liked most employees, making them well- evaluate not only the program but also the organization for the initiative.